Perlindungan Hukum bagi Perusahaan Akibat Wanprestasi dalam Perjanjian Kerja Sama (Studi Kasus di PT. Citra Mitra Sehati) Kota Bengkulu - Muhammad Gilang Anugrah Syahputra; Laily Ratna; Uswatun Hasanah (Lembaga Yasin AlSys, 2026)
Breach of contract in cooperation agreements is a legal issue that frequently occurs in the business sector because it may cause losses to parties that have fulfilled their obligations. This issue occurred in the cooperation relationship between PT Citra Mitra Sehati (PT CMS) and PT Bumi Cahaya Abhipraya Sehati (PT BCAS), when PT BCAS failed to fulfill its payment obligations for mining services that had been performed by PT CMS, resulting in financial and operational losses. This study aims to analyze the legal protection available to PT CMS as a result of breach of contract in its cooperation agreement with PT BCAS and to identify the factors causing the breach of contract. This study used empirical legal research with a qualitative approach. Data were obtained through interviews and document study, then analyzed descriptively and qualitatively. The results show that PT BCAS committed a breach of contract because it failed to fulfill its payment obligations as stipulated in Coal Mining Services Contract Number 003/CMS-BCAS/KONT-TAMB/02/2022. The legal protection available to PT CMS includes the right to issue a notice of default, demand performance, claim compensation, and request contract termination through non-litigation or litigation channels in accordance with the provisions of the Indonesian Civil Code. The factors causing the breach of contract include the weak good faith of the defaulting party, economic conditions, unclear contractual clauses, suboptimal supervision of contract implementation, difficulty in proving losses, the lengthy dispute resolution process, and the high cost of case settlement. The conclusion of the study affirms that legal protection for companies in cooperation agreements needs to be strengthened through the preparation of contracts that are clear, detailed, and oriented toward legal certainty. The implications of this study provide practical contributions for business actors in increasing contractual prudence, strengthening supervision of agreement implementation, and minimizing the risk of breach of contract in business cooperation.